2019
DOI: 10.1007/s00106-019-0663-1
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological intervention in the field of ototoxicity

Abstract: Modern research on ototoxicity goes back to the 1940s, when streptomycin was introduced into clinical practice. Today, aminoglycoside antibiotics and platinum-based chemotherapy, mainly cisplatin, are the most important drugs that damage the inner ear and cause hearing loss. The mode of drug administration as well as drug characteristics influence the likelihood that adequate monitoring of drug pharmacokinetics can be performed. It is not possible to predict the individual risk of treatment with an ototoxic dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 41 publications
0
17
0
5
Order By: Relevance
“…As mentioned in the kidney section of this review, aminoglycoside antibiotics and anticancer platinum agents, most notably gentamicin and cisplatin, respectively, are known for their nephrotoxicity and also to induce irreversible hearing loss. While it cannot be disputed that these agents lead to ototoxicity, since evidence for the relevance of OCT2 in these processes has been presented in both rodents and gineau pigs, literature on humans on this topic is not abundant [ 169 ]. Additionally, conflicting evidence has been presented as to the localization of OCT2 in the inner ear structures in the experimental models used [ 40 , 170 ].…”
Section: Octs In Other Tissuesmentioning
confidence: 99%
“…As mentioned in the kidney section of this review, aminoglycoside antibiotics and anticancer platinum agents, most notably gentamicin and cisplatin, respectively, are known for their nephrotoxicity and also to induce irreversible hearing loss. While it cannot be disputed that these agents lead to ototoxicity, since evidence for the relevance of OCT2 in these processes has been presented in both rodents and gineau pigs, literature on humans on this topic is not abundant [ 169 ]. Additionally, conflicting evidence has been presented as to the localization of OCT2 in the inner ear structures in the experimental models used [ 40 , 170 ].…”
Section: Octs In Other Tissuesmentioning
confidence: 99%
“…It is also worth noting that certain ototoxic medications might even be otoprotective against other ototoxic medications. 29 For instance, aspirin has been explored for the potential to mitigate the effects of hearing loss induced by intravenous gentamicin. 30 The study found that 3% of patients receiving aspirin had evidence of hearing loss compared with 13% in the placebo group.…”
Section: Mechanisms Of Ototoxicitymentioning
confidence: 99%
“…Although the mechanisms described previously are among those more commonly studied, other mechanisms of ototoxicity have yet to be investigated. It is also worth noting that certain ototoxic medications might even be otoprotective against other ototoxic medications 29 . For instance, aspirin has been explored for the potential to mitigate the effects of hearing loss induced by intravenous gentamicin 30 .…”
Section: Mechanisms Of Ototoxicitymentioning
confidence: 99%
“…Although an extensive number of preclinical studies have explored protective interventions to reduce cisplatin-induced ototoxicity, there are no generally established clinical guidelines. The challenges for translation of preclinical to clinical trials are: (1) differences in morphology and physiology between the human cochlea and that of experimental animals (Laurell, 2019); (2) identification of ototoxic susceptible patients in that international standards among classification systems do not exist (Knight et al, 2017).…”
Section: Clinical Trialsmentioning
confidence: 99%